Aspergillus terreus Meningitis in Immunocompetent Patient: A Case Report - Elsawy, Abdelrahman; Faidah, Hani; Ahmed, Abdalla; Mostafa, Asmaa; Mohamed, Farah (Frontiers in Microbiology, 2015)
We describe a rare but dangerous case of fungal meningitis due to Aspergillus terreus in immunocompetent man who had history of sinus disease.